2018
DOI: 10.1186/s40623-018-0821-9
|View full text |Cite
|
Sign up to set email alerts
|

Spread-F occurrences and relationships with foF2 and h′F at low- and mid-latitudes in China

Abstract: Ionospheric irregularities are an important phenomenon in scientific studies and applications of radio-wave propagation. Spread-F echoes in ionograms are a type of high-frequency band irregularities that include frequency spread-F (FSF), range spread-F (RSF), and mixed spread-F (MSF) events. In this study, we obtained spread-F data from four ionosondes at low-and mid-latitudes near the 120°E chain in China during the 23rd solar cycle. We used these data to investigate spread-F occurrence percentages and variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 60 publications
(76 reference statements)
0
15
0
Order By: Relevance
“…To summarize, there are few earlier investigations that report the occurrence of mid‐latitude irregularity structures using multiple instruments such as all‐sky airglow imager, VHF radar and ionosonde above 25°N/S of geomagnetic latitudes. In these studies, all‐sky airglow imagers (e.g., Garcia et al, ; Otsuka et al, ; Sahai et al, ) were used to show the MSTID structures whereas, VHF radar (e.g., Fukao et al, ; Otsuka et al, ; Swartz et al, ) or the ionosonde (e.g., Wang et al, ; Yang et al, ) observations were primarily used to identify the mid‐latitude FAIs/Spread‐F signatures. The present investigation reports a nearly geomagnetic field aligned (slightly tilted) westward drifting airglow depletion over 25°N geomagnetic latitude which is different from the previous investigations.…”
Section: Discussionmentioning
confidence: 99%
“…To summarize, there are few earlier investigations that report the occurrence of mid‐latitude irregularity structures using multiple instruments such as all‐sky airglow imager, VHF radar and ionosonde above 25°N/S of geomagnetic latitudes. In these studies, all‐sky airglow imagers (e.g., Garcia et al, ; Otsuka et al, ; Sahai et al, ) were used to show the MSTID structures whereas, VHF radar (e.g., Fukao et al, ; Otsuka et al, ; Swartz et al, ) or the ionosonde (e.g., Wang et al, ; Yang et al, ) observations were primarily used to identify the mid‐latitude FAIs/Spread‐F signatures. The present investigation reports a nearly geomagnetic field aligned (slightly tilted) westward drifting airglow depletion over 25°N geomagnetic latitude which is different from the previous investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The longitudinal and latitudinal effects of the spread-F occurrences at midlatitude have been discussed by many authors (Huang et al 2011;Kherani et al 2009;Wang et al 2018;Perkins 1973;Yakoyama et al 2008;Zhou et al 2005). They argued that AGW and Perkins instability may be the main mechanism for the occurrence and evolution of spread-F at midlatitude.…”
Section: Probable Mechanism Of Longitudinal and Latitudinal Differencmentioning
confidence: 99%
“…Spread-F has been widely studied since it was first defined on the ionogram in the early 1930s (Booker and Wells 1938). Several observations since then revealed the main morphological features of spread-F occurrence, including its dependences on solar and magnetic activities, season, longitude, latitude, local time and the background ionosphere (Aarons et al 1980;Abdu et al 1981Abdu et al , 1983Abdu et al , 1998Fukao et al 2004;Li et al 2013;Lynn et al 2011;Wang et al 2007Wang et al , 2018Xu et al 2010). Previous studies have focused on low latitudes especially for the equatorial region.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical characteristics of nighttime SF have been studied over the past several decades. Earlier observational evidences suggested that the occurrence of SF at equator and low latitudes has obvious diurnal, latitudinal, longitudinal, seasonal, solar cycle and geomagnetic activity variations (Abdu et al 1981(Abdu et al , 1985Li et al 2010;Upadhayaya and Gupta 2014;Rungraengwajiake et al 2013;Wang et al 2010;Dabas et al 2007;Zhu et al 2015;Wang et al 2018). Pezzopane et al (2013) performed a comparative analysis of equinoctial SF characteristics at different longitude sectors at low latitudes using observations of ionosonde.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the negative correlations between Kp and RSF, MSF and SSF were also presented in their work, except FSF. On the other hand, Wang et al (2018), Dabas et al (2007) and Rungraengwajiake et al (2013) carried out comparative analysis of SF recorded by ionosondes at different latitudinal regions. Their results showed that RSF was dominant over the stations near equator which occurred mostly in equinoxes and at post-sunset.…”
Section: Introductionmentioning
confidence: 99%